The Effectiveness of the Thematic Module Based on the Qur'an and Hadith with the Thematic Package Book on Learning Outcomes and Religious Characters of Grade 4 Students - Nuril Nuzulia (Madrosatuna: Journal of Islamic Elementary School, 2017)
The module is one of the teaching material media that is intact and systematic. This study aims to determine the effectiveness of teaching thematic modules based on the Qur'an and Hadith with the thematic package book on the 4th class religious character in SDN Janti 2 Tarik Sidoarjo. The type of research is experimental research with samples taken by class 4 A (experimental class with thematic learning module based on qur'an and hadith) and 4 B (control class with thematic package book). The data were obtained from the students' learning outcomes of the cognitive and affective aspects of my dream ideals by analyzing using SPSS program statistics. The result of cognitive domain using SPSS Independent Samples Test shows the significance of 0.000 <0,05 then Ho is rejected so it can be concluded that there is effectiveness of thematic teaching module based on qur'an and hadith with thematic package book to the result of fourth grade student learning at SDN Janti 2 Pull Sidoarjo. Likewise, the affective domain results show the percentage of 90% so it can be concluded to increase students' religious kararkter. Learning module has a high influence, seen from the cognitive domain learning results obtained by an average score of 80, while affective domain average value 4. For thematic package books have a lower effect because of the cognitive domain learning results obtained an average of 75, while affective domains result in an average value of 3.